HUMANISME PROGRESIF DALAM FILSAFAT PENDIDIKAN ISLAM - Wedra Aprison (Jurnal Pendidikan Islam, 2012)
This paper tries to simplify the schools of philosophy of education into three mainstreams only: constructivism, leberalism and anarchism, it is also to pave the way that enables philosophy of Islamic education play its role by finding out the interplay among those three mainstreams and then analysing them in the context of Islam. Those three share the same conceptions regarding religiosity/tawheed and humanism/ good deeds. When the two points are confronted with the issues of education and community, new challenges emerge: that is, the philosophy of Islamic education except religious and humanist must also be progressive in advancing civilization through the spirit of diversity that exists within a nation or between nations. Philosophically, the result of the synthesis is called progressive humanism philosophy of Islamic education. The approach and methods used in this paper is a content analysis of the philosophical and theological education. Philosophical education analyzed is O'neil thought about educational ideologies. Theological analysis used as tool of analysis is Abu Zaid‟s thought (2003) regarding the importance of reasoning power of the word of God which is then grounded by Setiawan (2012) as a Progressive Islam.